FORMULASI KRIM EKSTRAK PROPOLIS DAN EVALUASI AKTIVITAS ANTIOKSIDAN IN VITRO SERTA UJI IRITASI IN VIVO - Dwi Santiani Lubis, Amalia
Propolis contain some antioxidant compounds, such as phenols and flavonoids, nevertheless the use of propolis as antioxidant in cosmetics formulation is less common. The objectives of this research were to determine the IC50 of ethanol extract of propolis, to determine antioxidant activity of ethanol extract of propolis in cream formulation, and to compare its activity in two different o/w cream formulations by using DPPH method. Primary irritation test was conducted to evaluate the safety of this preparation. Crude drug was extracted by reflux method using 70% ethanol as solvent. Propolis ethanol extract was monitored by thin layer chromatography (TLC). Total phenolic content and flavonoid content were also determined. Antioxidant activity was determined using DPPH method. DPPH (2,2-dipheny1-1-picrylhydrazil) scavenging activity was measured and determination of IC50 was performed with ascorbic acid as positive standard. Concentrated extract was mixed in to two different cream formulations that have been optimized previously. Both formulas were o/w cream with same composition of extract and excipients. The difference between these formulas was on the oil phase. Formula 1 contained liquid paraffin while formula 2 contained Virgin Coconut Oil (VCO). Stability test was conducted in two different temperature, room temperature (25°C) and climatic chamber (40°C). The parameters that were evaluated including organoleptic (color, smell, separation), freeze and thaw stability test, pH, viscosity, DPPH scavenging activity, and primary irritation test using rabbit skin as medium. Based on phytochemical screening, propolis contained flavonoid, phenol, quinon, and steroid/triterpenoid. Ethanol extract of propolis (density of 1% extract 0,81 g/mL) showed high DPPH scavenging activity with IC50 36,9 pig/mL while ascorbic acid's IC50 8,85 tig/mL, total phenolic content 14,97 g GAE/I00 g, and total flavonoid content 2,12 g QE/100 g. Final formula used in the making of propolis cream consist of propolis extract 3,7%, sodium lauryl sulphat 1%, cetostearyl alkohol 9%, liquid paraffin / VCO 20%, propylene glicol 15%, and ethanol 5%. Propolis cream showed good physical stability. DPPH radical scavenging activity percentage of cream Fl during the observation was 38,71% - 54,57% and cream F2 was 42,18% - 52,74%. Radical scavenging activity of F1 and F2 showed no significant difference based on one-way ANOVA with LSD method. Refers to safety evaluation by primary irritation test, propolis cream primary irritation index (OECD) was 0. Ethanol extract of propolis showed high potency as antioxidant (IC50 36,9 j.ig/mL) while ascorbic acid's IC50 8,85 tg/mL. Final formula used in making propolis cream consist of propolis extract 3,7%, sodium lauryl sulphat 1%, cetostearyl alkohol 9%, liquid paraffin / VCO 20%, propylene glicol 15%, ethanol 5%, methyl paraben 0,18%, propyl paraben 0,02%, dun aquades ad 100%. DPPH radical scavenging activity percentage of cream Fl during the observation was 38,71% - 54,57% and cream F2 was 42,18% - 52,74%. Radical scavenging activity of FI and F2 showed no significant difference based on one-way ANOVA with LSD method. Propolis cream was proven to be safe by primary irritation test with the value of primary irritation index (OECD) was 0.